Ukuran Perusahaan Memoderasi Pengaruh Free Cash Flow dan Leverage Terhadap Kebijakan Dividen - Trisna, I Kadek Edi Rian; Gayatri, Gayatri (E-Jurnal Akuntansi, 2019)
Determining the optimal cash dividend policy a company should consider several factors. An optimal dividend policy is required because it can create a balance between dividends and current growth in the next period. The purpose of this study is to obtain empirical evidence on the effect of free cash flow and leverage on dividend policy and firm size capability in moderating the effect of free cash flow and leverage against dividend policy. Companies going public listed on the Indonesia Stock Exchange (BEI) year 2013-2017 is the location of research with purposive sampling as a method of determining the sample. Companies that meet the criteria are 10 companies with a total of 39 observations. Moderated Regression Analysis (MRA) was used to test in this research. The result showed that free cash flow had positive and leverage effect negatively on dividend policy. The study also found that firm size is able to strengthen the effect of free cash flow on dividend policy and weaken the influence of leverage on dividend policy. Keywords : dividend policy, free cash flow, leverage, company size. .